An undescribed lowland natural forest at Bodogol, Gunung Gede Pangrango National Park, Cibodas Biosphere Reserve, West Java, Indonesia - Nelva Helmi; Kuswata Kartawinata; Ismayadi Samsoedin (REINWARDTIA, 2009)
An analysis of the structure and floristic composition of trees with diameters at breast height ? 10 cm in a one- hectare plot in a lowland natural forest at the elevation of 800 m at Bodogol, the Gunung Gede Pangrango National Park, Cibodas Biosphere Reserve, recorded 70 spesies and 30 families with a density of 350 trees/hectare and a total basal area of 23.36 m2. As high as 37 tree spesies (52.86 %) were not recorded in the flora of Mt.Gede Pangrango; they were species of upper lowland forest and dominated the plot. Among 10 main species, only Altingia excelsa and Ficus ribes are montane forest species. Thus the forest plot represents a transition between lowland forest and lower montane forest, which may be called an upper lowland forest. This is a new phenomenon which has not been recorded previ- ously at the Gunung Gede Pangrango National Park. The most prominent species with Importance Value (VI) > 10 % are Schima wallichii, Pternandra caerulescens, Neesia altissima, Luvunga sarmentosa and Maesopsis eminii; the latter is an exotic species invading the natural forest. Dipterocarpus hasseltii is present in the area.